2009
DOI: 10.1038/sj.bjc.6605098
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in British vegetarians

Abstract: BACKGROUND: Few prospective studies have examined cancer incidence among vegetarians. METHODS: We studied 61 566 British men and women, comprising 32 403 meat eaters, 8562 non-meat eaters who did eat fish ('fish eaters') and 20 601 vegetarians. After an average follow-up of 12.2 years, there were 3350 incident cancers of which 2204 were among meat eaters, 317 among fish eaters and 829 among vegetarians. Relative risks (RRs) were estimated by Cox regression, stratified by sex and recruitment protocol and adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 20 publications
4
96
0
4
Order By: Relevance
“…In contrast, vegetables decreased risk for hypertension, obesity, diabetes, CVD and some cancers (31)(32)(33)(34)(35) . Based on considerable research (36)(37)(38) , the dietary recommendations for prevention of chronic diseases advised limiting the consumption of red and processed meat and to eat mostly plant-based food.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, vegetables decreased risk for hypertension, obesity, diabetes, CVD and some cancers (31)(32)(33)(34)(35) . Based on considerable research (36)(37)(38) , the dietary recommendations for prevention of chronic diseases advised limiting the consumption of red and processed meat and to eat mostly plant-based food.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, epidemiological data suggest that cancer incidence is lower in vegetarians compared with nonvegetarians, although results are inconsistent (27,30,31) and probably depend on cancer site. The largest prospective study of 34 192 Seventh Day Adventists suggested cancer of the colon (relative risk (RR)51?88, 95 % CI 1?24, 2?87; P 5 0?003) and prostate (RR 5 1?54, 95 % CI 1?05, 2?26; P 5 0?03) were significantly more likely in omnivores than in vegetarians (27) although this was not confirmed in a recent pooled analysis from two UK populations (30) . The Adventist study showed no difference in breast cancer incidence (RR 5 1?25, 95 % CI 0?87, 1?80; P 5 0?22) between vegetarians and non-vegetarians (27) .…”
Section: What Is a Vegetarian Diet?mentioning
confidence: 99%
“…The dietary fiber theory of Mr. Burkitt spawned thousands of case-control, cohort and randomized intervention trials over the next three decades. As it happens with good scientific research practises, almost all the large studies with designs to minimize bias and confounding failed to provide consistent results or substantial reduction in CRC with diet high in fruits and vegetables [17][18][19][20][21][22][23]. The first credible report showing no protective effect of a vegetarian diet against CRC was a meta-analysis of 5 prospective studies of vegetarians living in Western countries [17].…”
mentioning
confidence: 99%
“…The first credible report showing no protective effect of a vegetarian diet against CRC was a meta-analysis of 5 prospective studies of vegetarians living in Western countries [17]. A more recent study of British vegetarians found a 12% non significant increase in CRC among the vegetarians in comparison to meat eaters [18]. The multi European EPIC study which followed 142,605 men and 335,873 women for a median of 8.7 years showed a small inverse association between intake of total fruits and vegetables and CRC risk in non tobacco users [19].…”
mentioning
confidence: 99%